The Use of Oral Literature Kei in the Rafak Rahan Tradition in Yamtel Village - Ubjaan, Edheledia (Universitas Pattimura, 2023)
The rafak rahan tradition is a tradition retained by the Kei people, rich in oral literature. The rafak rahan tradition, or house-closing tradition, represents a ritual of the Kei people: erecting a new dwelling. In the last stage of the new house construction process (covering the new house with tiles), a customary ceremony will be held by the closest relatives, especially for daughters or sisters who have been separated from their dads or brothers due to marriage. This traditional holiday is distinguished by the giving of gifts such as gold, cloth, and dishes (Mas, Sobo, Began), which the Kei community, especially the Yamtel people, believe are symbolic of familial relationships. Additionally, there are Kei kubil or cookies, which are a typical dish of the Kei people, prepared specifically and only available during the customary rafak rahan or house closure ceremony. Based on the preceding definition, this study analyzes the usage of oral literature in the rafak rahan tradition. The data gathering techniques employed are observation techniques, interview techniques, recording techniques, field note techniques, and documentation. Data were evaluated as follows: (1) Data reduction, which is the process of selecting and focusing on reducing, abstracting, and modifying data that occurs in written field notes. Data reduction is part of data analysis, a form of analysis that sharpens, categorizes, directs, discards unneeded data, and organizes data so that final conclusions can be reached and validated. (2) Data presentation is the second step in data analysis, which is a collection of information regarding the study completed, enabling for conclusions to be reached and actions to be taken. (3) Conclusion. The orderly collecting of information allows for conclusions to be reached and actions to be implemented. Drawing conclusions is merely half of an action. The conclusions were also validated during the research. The analytical results suggest that in Kei society, the rafak rahan tradition is a tradition that has existed for hundreds of years and has been passed down by ancestors, thus it must be honored and its existence safeguarded. In actuality, this rafak rahan tradition is not merely an idea that was developed hundreds of years ago and passed down through generations. The rafak rahan tradition comprises values of mutual collaboration, working together, or supporting each other, which is recognized as maren among the Kei people. The facts uncovered include that the rafak rahan tradition and the usage of oral literature, which are old traditions, are still practiced by the Yamtel group to this day.